Achieving Inclusive Development: Bridging Gender Equality and Social Inclusion (GESI) in Indonesia’s Rural and Urban Communities - Sari, Anneke Zehan Puspita; Antik Bintari (Universitas Ekasakti, 2024)
This article explores the challenges and strategies for achieving inclusive development in Indonesia, focusing on the integration of Gender Equality and Social Inclusion (GESI) principles in rural and urban areas. It examines the disparity in development indicators across regions and the effectiveness of policies like the Desa Ramah Perempuan dan Peduli Anak (DRPPA) program. The study highlights the role of government and community in fostering equitable growth and addresses the impact of gender stereotypes and social exclusion on development efforts. By analyzing current policies and their implementation, the article provides insights into improving GESI integration for sustainable and inclusive development in Indonesia.